2011
DOI: 10.1007/978-1-4614-3290-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Venus, Mars, and Titan

Abstract: Increased computer capacity has made it possible to model the global plasma and neutral dynamics near Venus, Mars and Saturn's moon Titan. The plasma interactions at Venus, Mars, and Titan are similar because each possess a substantial atmosphere but lacks a global internally generated magnetic field. In this article three self-consistent plasma models are described: the magnetohydrodynamic (MHD) model, the hybrid model and the fully kinetic plasma model. are also described. In particular, we describe the pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 151 publications
1
12
0
Order By: Relevance
“…This approach, although more binding in terms of computational resources than a fluid model, is based on less assumption and include more physics (Hall term, Larmor radius effect, etc.). A complete review of these formalisms, their respective assumptions and limitations are detailed in Ledvina et al [], Kallio et al [], and Winske et al [].…”
Section: Simulation Modelmentioning
confidence: 99%
“…This approach, although more binding in terms of computational resources than a fluid model, is based on less assumption and include more physics (Hall term, Larmor radius effect, etc.). A complete review of these formalisms, their respective assumptions and limitations are detailed in Ledvina et al [], Kallio et al [], and Winske et al [].…”
Section: Simulation Modelmentioning
confidence: 99%
“…In addition to the theoretic analysis, numerical simulations (e.g., MHD simulations and hybrid simulations) performed to study the induced magnetosphere may help to provide hints to understand the tail configuration, although derived simulation results must be interpreted with caution [ Kallio et al ., ]. Hybrid simulations of Titan [ Simon and Motschmann , ] and Venus [ Kallio et al ., ] showed that the current sheet of the induced magnetotail would be displaced when there is a corresponding IMF flow‐aligned component.…”
Section: Discussionmentioning
confidence: 99%
“…The CEM can be biased at different potentials ranging from 1000 to 2500 V. The gain of the CEM is a function of both the bias voltage and the ion mass; the typical gain for CEM is ~10 5 . Partial pressures of ~10 -14 torr can be measured with the CEM.…”
Section: Instrumentmentioning
confidence: 99%
“…The Martian exosphere starts from an altitude of ~250 km (ref. 5). The only inferences drawn on the Martian exosphere, so far, have been on its total number density based on spacecraft drag measurements and few studies on the extent of hydrogen 6 and oxygen exospheres 7 based on their respective spectral emission signatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation